Pragmatic Archaeology and Semiotic Mediation - Robert Preucel (Semiotic Review, 2016)
Archaeology is a semiotic enterprise engaged in the study of meaning-making practices by past actors and of archaeologists themselves. Archaeology embraced its semiotic character in the context of the processual and postprocessual debates, and in terms of various postprocessual developments. Recently some archaeologists have drawn inspiration from the material semiotics of Bruno Latour to advocate for a symmetrical archaeology. This perspective offers a novel approach to object agency and focuses on how objects and humans together form assemblages. However, it neglects a satisfying account of how objects and things transform each other. One productive way forward is a consideration of semiotic mediation offered by a pragmatic archaeology linked to the work of Charles Sanders Peirce.